Fungal infections of the orbit - Bipasha Mukherjee; Nirav Dilip Raichura; Md Shahid Alam (Indian Journal of Ophthalmology, 2016)
Fungal infections of the orbit can lead to grave complications. Although the primary site of inoculation of the infective organism is frequently the sinuses, the patients can initially present to the ophthalmologist with ocular signs and symptoms. Due to its varied and nonspecific clinical features, especially in the early stages, patients are frequently misdiagnosed and even treated with steroids which worsen the situation leading to dire consequences. Ophthalmologists should be familiar with the clinical spectrum of disease and the variable presentation of this infection, as early diagnosis and rapid institution of appropriate therapy are crucial elements in the management of this invasive sino-orbital infection. In this review, relevant clinical, microbiological, and imaging findings are discussed along with the current consensus on local and systemic management. We review the recent literature and provide a comprehensive analysis. In the immunocompromised, as well as in healthy patients, a high index of suspicion must be maintained as delay in diagnosis of fungal pathology may lead to disfiguring morbidity or even mortality. Obtaining adequate diagnostic material for pathological and microbiological examination is critical. Newer methods of therapy, particularly oral voriconazole and topical amphotericin B, may be beneficial in selected patients.